Model of political player's profile Study of the human element in turbulent organizations - Acevedo Borrego, Adolfo (2009)
There are organizations, known as political parties, that influencing the government, businesses, industries, and virtually crossing all fields of society. Their members have strengths that allow them to play in turbulent environments with undefined problems. Otherwise, the professional technical has weaknesses to interact when the environment is complex and problems are soft unstructured. Since the working hypothesis, “the activists of political parties have a similar profile that allows them to act effectively in diverse environments”, we design a construct and a conceptual model to identify the variables that shape the success of these. This article shows the progress of empirical qualitative research, it attempts to describe the profile of political activist and their strengths, which are required to operate adequately in changing environments.